2015
DOI: 10.5114/pjp.2015.53013
|View full text |Cite
|
Sign up to set email alerts
|

Original paper Evaluation of the role of Epstein-Barr virus in cases of nodal or extranodal T- and NK-cell lymphoma using eber in situ hybridization

Abstract: Various racial and geographic differences have been observed in studies questioning the role of Epstein-Barr virus (EBV) infection in the etiology of T-and NK-cell lymphomas. The aim of this study was to evaluate the relationship of EBV with nodal or extranodal (skin excluded) T-and NK-cell lymphoma subtypes encountered in our geographic area. Sixty-two cases of peripheral T-cell lymphoma were included in the study. EBV-encoded early RNA (EBER) was detected by in situ hybridization. The distributions of T-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…2 With a cut-off value of > 25% EBER-positive neoplastic cells, EBV positivity of PTCL-NOS was reported to be 5-31%. 21,22 On the other hand, EBV was detected in 6% of PTCL-NOS with a cut-off value of > 50% EBER-positive neoplastic cells. 21 The clinicopathological features of nodal EBV + CTL in previous studies (more than 10 cases) are summarized in Table 2.…”
Section: Epidemiologymentioning
confidence: 99%
“…2 With a cut-off value of > 25% EBER-positive neoplastic cells, EBV positivity of PTCL-NOS was reported to be 5-31%. 21,22 On the other hand, EBV was detected in 6% of PTCL-NOS with a cut-off value of > 50% EBER-positive neoplastic cells. 21 The clinicopathological features of nodal EBV + CTL in previous studies (more than 10 cases) are summarized in Table 2.…”
Section: Epidemiologymentioning
confidence: 99%
“…ere were 17 cases graded as 4+, representing >75% EBER-positive neoplastic cells. Other ISH studies have reported EBER reactivity in 22.6% (14/62) of nodal or extranodal T-and NK-cell lymphomas cases [13], with the highest reactivity (30.1%) being in breast tumors [27] and the lowest reactivity (10%) being in gastric tumors (10%) [28]. Considering the strong Table 4: e relationship between the grade and tumor basal dimension in EBER-positive SGC of the eyelid.…”
Section: Discussionmentioning
confidence: 93%
“…e images were photographed using a digital camera attached to an Olympus BX1 light microscope (Tokyo, Japan). Referring to the previous article [13], the criteria used in scoring and grading the intensity of the EBER staining is as follows. (Figure 1 Grades 2+, 3+, and 4+, with a cutoff value of >5% EBERpositive neoplastic cells, were considered EBV positive, and grade 1+, with inadequate or equivocal positive neoplastic cells (a cut-off value <5%), were excluded from this study.…”
Section: Detection Of Ebermentioning
confidence: 99%
“…Compared to conventional plain radiography, CT scanning has become a valuable tool for diagnosing, comparing, and staging of ENKTL [ 14 ]. Many studies have pointed out that LMP1 may serve as a potential indicator for ENKTL [ 27 29 ]. Therefore, we aimed to investigate whether ENKTL can differentiate between nasal polyps and inverted papilloma arising in the nasal cavity by comparison of the CT imaging and the expression of LMP1.…”
Section: Discussionmentioning
confidence: 99%